Central Venous Catheter Utilization and Complications in the Pediatric Cardiac ICU: A Report From the Pediatric Cardiac Critical Care Consortium (PC4)*. Issue 8 (August 2020) - DiPietro, Lisa M.; Gaies, Michael; Banerjee, Mousumi; Donohue, Janet E.; Zhang, Wenying; DeSena, Holly C.; Graham, Eric M.; Sasaki, Jun; Moga, Michael-Alice; Prodhan, Parthak; Goldstein, Stuart L.; Tabbutt, Sarah; et al.
Abstract : Objectives: Current central venous catheter utilization in patients within pediatric cardiac ICUs is not well elucidated. We aim to describe current use of central venous catheters in a multi-institutional cohort and to explore the prevalence and risk factors for central line–associated thrombosis and central line–associated bloodstream infections. Design: Observational analysis. Setting: Pediatric Cardiac Critical Care Consortium hospitals. Patients: Hospitalizations with at least one cardiac ICU admission from October 2013 to July 2016. Interventions: None. Measurements and Main Results: There were 17, 846 hospitalizations and 69% included greater than or equal to one central venous catheter. Central venous catheter use was higher in younger patients (86% neonates). Surgical hospitalizations included at least one central venous catheter 88% of the time compared with 35% of medical hospitalizations. The most common location for central venous catheters was internal jugular (46%). Central venous catheters were in situ a median of 4 days (interquartile range, 2–10). There were 248 hospitalizations (2% overall, 1.8% medical, and 2.1% surgical) with at least one central line–associated thrombosis (271 total thromboses). Thrombosis was diagnosed at a median of 7 days (interquartile range, 4–14) after catheter insertion. There were 127 hospitalizations (1% overall, 1.4% medical, and 1% surgical) with at least one central line–associated bloodstream infection (136 total infections) with no association with catheter type or location. Central line–associated bloodstream infection was diagnosed at a median of 19 days (interquartile range, 8–36) after catheter insertion. Significant risk factors for central line–associated thrombosis and central line–associated bloodstream infection were younger age, greater surgical complexity, and total catheter days. Conclusions: Utilization of central venous catheters in pediatric cardiac ICUs differs according to indication for hospitalization. Although thrombosis and central line–associated bloodstream infection are infrequent complications of central venous catheter use in cardiac ICU patients, these events can have important short- and long-term consequences for patients. Total central venous catheter line days were the only modifiable risk factor identified. Future study must focus on understanding central venous catheter practices in high-risk patient subgroups that reduce the prevalence of thrombosis and central line–associated bloodstream infection. Abstract : Supplemental Digital Content is available in the text.